Food and nutritional security by sustainable agriculture Methods to attain and sustain - Tiwari, Jagesh Kumar; Kumar, Sunil; Mishra, B. K. & Others (New Delhi New India Publishing Agency, 2014)
1) Genetic improvement of crop plants : conventional and modern techniques